Optimal monitoring of anti epileptic drugs in pregnancy: time for a randomised controlled trial?. (7th June 2011) - Thangaratinam, S; Rikunenko, R; Greenhill, L; Bagary, M; Pirie, A; Khan, K S; McCorry, D
Abstract : Background: Pregnant women with epilepsy have a tenfold increased risk of mortality compared to other women, with 1 in 250 pregnancies exposed to antiepileptic drugs (AED). The levels of AED fall in pregnancy with a risk of worsening seizures. There is a clinical equipoise regarding the optimal AED monitoring method. Clinicians either regularly check serum levels of AED (therapeutic drug monitoring (TDM)) or adjust the AED dose based on clinical features alone (clinical features monitoring (CFM)). Aim: To evaluate the effectiveness of the AED monitoring regimes in pregnancy in reducing seizures. To ascertain the views of epilepsy professionals and pregnant women with epilepsy. Methods: We searched MEDLINE (1966–2010), EMBASE (1980–2010) and Cochrane (2009), for citations on the effectiveness of the two monitoring methods in pregnancy. We conducted an online survey of epilepsy professionals and also obtained the views of pregnant women attending the joint epilepsy obstetric clinic. Results: Five studies of pregnant women with epilepsy on lamotrigine (n=99) were included. The rate of seizure deterioration was 0.40 (95% CI 0.26 to 0.55) in women monitored by TDM compared to 0.73 (95% CI 0.56 to 0.86) in those monitored by CFM. A total of 27.6% (n=8) of epilepsy specialists practiced TDM, 62.1% (n=18) undertake TDM occasionally and 10.3% (n=3) practiced CFM. Over 96% of women (n=49/51) felt that the question was important for further research. Conclusion: Our work in this area has highlighted the need for a large clinical trial to provide definitive evidence.